The Influence of Tourists’ Motivation on Intention to Revisit at The Traditional Village of Prai Ijing, Waikabubak, West Sumba, East Nusa Tenggara - Fila Hidayana, Fransiska; Suryawardani, I Gusti Ayu Oka; Wiranatha, Agung Suryawan (E-Journal of Tourism; Volume 6 Number 2 (September 2019)DO - 10.24922/eot.v6i2.53750, 2019)
Push and pull factor as motivation for travelling are the components that influence tourist perception about tourist attraction related to the level of tourist satisfaction. Motivation also able to encourage tourist to revisit. Prai Ijing Traditional Village is one of the tourist attractions and cultural sites which is located in Waikabubak, West Sumba, NTT. It has unique culture, strategic location, therefore visited by many visitors. The purpose of this study is to determine the effect between motivation, tourist satisfaction and intention to revisit the village. The research method, the population of this research are domestic and foreign tourists visiting the Prai Ijing Traditional Village. The samples of this research is 100 visitors as the respondent, by using accidental sampling. The data were analyzed by Structural Equation Modeling (SEM) using SmartPLS software version 3.0 and qualitative descriptive analysis to describe the characteristics of respondents, interpretate the results of SEM analysis, and reveal the result of research hypothesis test. The results showed that push and pull factors had significant effect on tourist satisfaction. Tourist satisfaction had significant effect on the intention to revisit. The push and pull factors did not had significant effect on the intention to revisit.  Pull factors had significant effect than push factors on tourist satisfaction. Therefore, the pull factors need to be maintained and improved in order to be able to provide optimal satisfaction. The management and local communities are expected to increase the diversity of attraction and tourist activities, provide unique and innovative cultural tourism products, and maintain local wisdom and cultural assets as the main attention for tourists to visit the Prai Ijing Traditional Village Keywords: tourist motivation, satisfaction, revisit intention, SEM